2010
DOI: 10.1016/j.pbb.2009.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone differentially alters cocaine-induced ambulatory and rearing behavioral responses in adult and adolescent rats

Abstract: Little is known about the physiological and behavioral effects of testosterone when co-administered with cocaine during adolescence. The present study aimed to determine whether exogenous testosterone administration differentially alters psychomotor responses to cocaine in adolescent and adult male rats. To this end, intact adolescent (30-days-old) and adult (60-day-old) male Fisher rats were pretreated with vehicle (sesame oil) or testosterone (5 or 10 mg/kg) 45 minutes prior to saline or cocaine (20 mg/kg) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
4
5
1
Order By: Relevance
“…Differently from our results, Minerly et al (2010) demonstrated that adolescent rats showed an increase in cocaine-induced locomotor activity after a single injection of testosterone propionate (5 or 10 mg/kg). In the same way, Martinez-Sanchis et al (2002) demonstrated, in adolescent mice, that acute testosterone administration resulted in increased locomotor response to cocaine.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Differently from our results, Minerly et al (2010) demonstrated that adolescent rats showed an increase in cocaine-induced locomotor activity after a single injection of testosterone propionate (5 or 10 mg/kg). In the same way, Martinez-Sanchis et al (2002) demonstrated, in adolescent mice, that acute testosterone administration resulted in increased locomotor response to cocaine.…”
Section: Discussioncontrasting
confidence: 99%
“…The dose of cocaine used in these experiments is known to induce locomotor activity in the absence of focused stereotypy (Marin et al, 2008; Ushijima et al, 1995). The dose of testosterone was previously shown to change cocaine‐induced locomotor activity and is consistent with the abuse dosage used for humans (Martinez‐Sanchis et al, 2002; Minerly et al, 2010).…”
Section: Methodssupporting
confidence: 62%
See 1 more Smart Citation
“…We were unable to locate any clinical studies of the interactions between cocaine and testosterone. As noted earlier, findings from preclinical studies of the effects of testosterone on cocaine-related increases in locomotor activity in rodents were inconsistent (Long et al, 1994;Martinez-Sanchis et al, 2002;Minerly et al, 2010). In this study, testosterone, like progesterone, produced a significant dose-dependent decrease in cocaine self-administration in female rhesus monkeys.…”
Section: Interactions Between Cocaine and Neuroactive Steroid Hormonesmentioning
confidence: 46%
“…Testosterone was reported to enhance (Martinez-Sanchis et al, 2002;Minerly et al, 2010) and to prevent cocaineinduced locomotor activity (Long et al, 1994). Testosterone was reinforcing in rodents under some conditions (see for a review, Wood, 2004).…”
Section: Introductionmentioning
confidence: 99%